Nivel de satisfacción de los pacientes hospitalizados, respecto a la dieta del Hospital San Vicente de Paúl de Ibarra, 2018: Level of satisfaction of hospitalized patients, regarding the diet of the hospital San Vicente de Paúl de Ibarra, 2018 (La U Investiga, 2019)
The recovery of the hospitalized patient depends on the dietary therapy intervention and the food service is responsible for this, but your opinion as a user is also key to evaluating the quality of the service. This study determined the level of satisfaction of hospitalized patients regarding the diet provided by the Nutrition and Dietetics Service of the Hospital San Vicente de Paúl (HSVP) in Ibarra, 2018. It was a descriptive cross-sectional study in 200 patients, The Acute Care Hospital Foodservice Patient Satisfaction Questionnaire was adapted, and sociodemographic and hospital data were also collected. 61.5% were women; age 46.5 ± 12.1 years; hospital stay
Keywords: satisfaction; diet; patient; hospital